Assessment of natural radioactivity in urban soil samples from Dhaka city and its associated health hazard - Shikha Pervin; Nadia Sarker; Md. Masum Haider; Shanjib Karmaker; Tanzeem Tahmeed Reza; Selina Yeasmin; Mayeen Uddin Khandaker (PLoS ONE, 2026)
Humans are constantly exposed to radiation from their natural environment including soil and gamma radiation has harmful effects on them, so determination of radioactivity concentration in soil are very important. The present study aims to measure the activity concentrations of naturally occurring radionuclides 226 Ra, 232 Th, and 40 K in urban soil samples collected from thirty different areas of Dhaka city. The analyzed was performed using a High-Purity Germanium (HPGe) gamma-ray spectrometer. The results showed that the mean activity concentrations of 226 Ra, 232 Th, and 40 K were found 24.2 ± 1.0 Bqkg -1 , 52.0 ± 2.0 Bqkg -1 , and 352 ± 11 Bqkg -1 , respectively. The average concentrations of 226 Ra and 40 K fall below the internationally recommended safety limits of 35 Bqkg -1 and 400 Bqkg -1 , respectively, while 232 Th value exceeded the recommended limit of 30 Bqkg -1 by approximately 1.7 times. The mean value of radium equivalent activity (Ra eq ) was calculated as 125.7 Bqkg -1 , which was far below the global safety threshold of 370 Bqkg -1 . The estimated outdoor effective dose rates were 0.070 mSvy -1 and below the worldwide recommended limit of 1 mSvy -1 . Additionally, excess life time cancer risk (ELCR) was below than the internationally accepted limit of 0.29 × 10 −3 . All things considered, the study is the first comprehensive dataset of urban soil in the area and revealed that there are no immediate health dangers due to the low radioactive hazard indices.